2011
DOI: 10.1002/app.33307
|View full text |Cite
|
Sign up to set email alerts
|

Properties of bacterial cellulose produced in grape medium by native isolate Gluconacetobacter sp

Abstract: During the production of grape wine, the occurrence of thick leathery pellicle at the air‐liquid interface was found as a contaminant. The pellicle produced was investigated with a view to use as biodegradable polymer. The bacterium that is responsible for the pellicle production was isolated, characterized and identified as Gluconacetobacter sp. Pellicle was produced in pasteurized grape extract as well as in HS medium by the isolated organism in static conditions. The purified film was subjected for Fourier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 26 publications
5
16
0
Order By: Relevance
“…were isolated from kombucha tea, one of fermented beverages. Rani, Udayasankar, and Appaiah (2011) found that the pellicle formed in contaminated grape wine. The bacterium forming the pellicle production was isolated, characterized and identified as Gluconacetobacter sp.…”
Section: Introductionmentioning
confidence: 97%
“…were isolated from kombucha tea, one of fermented beverages. Rani, Udayasankar, and Appaiah (2011) found that the pellicle formed in contaminated grape wine. The bacterium forming the pellicle production was isolated, characterized and identified as Gluconacetobacter sp.…”
Section: Introductionmentioning
confidence: 97%
“…Films of 25 μm thickness were found to have an unusually high tensile strength of 41 MPa and elongation of 0.98 mm. The films had low oxygen permeability but high water permeability [11Ran]. Figure 61.10 shows an SEM image of the bacterial cellulose generated by the cells.…”
Section: Agricultural Residues As Feedstocks For Production Of Bactermentioning
confidence: 98%
“…Morphologically, the fibers had a rough surface with pores in the middle that were responsible for the poor tensile strength. Bacterial cellulose had unique properties such as high porosity, high purity and crystallinity, good mechanical properties and high water holding capacity, excellent biodegradability, and biocompatibility [12Wan] which make it [11Ran] preferable for applications in batteries, sensors, electrical devices, and antistatic coating. To utilize these advantages, bacterial cellulose in nanofiber form was blended with poly(aniline) and made into composites with flake shaped morphology with high electrical conductivity.…”
Section: Blends Of Bacterial Cellulose Fibersmentioning
confidence: 99%
“…[5][6][7][8]. At present, bacterial strains such as Agrobacterium, Rhizobium, Acetobacter, Aerobacter, Gluconacetobacter have been reported for BC production under optimum bioprocess conditions [9][10][11][12]. Acetobacter xylinum is one of the most extensively studied sources of BC [13].…”
mentioning
confidence: 99%